The role of NLRP3 inflammasome-mediated pyroptosis in ischemic stroke and the intervention of traditional Chinese medicine - Jia-Xin Long; Meng-Zhi Tian; Xiao-Yi Chen; Huang-He Yu; Huang Ding; Fang Liu; Ke Du (Frontiers Media S.A., 2023)
Ischemic stroke (IS) is the second leading cause of death and disability in the world. Pyroptosis, a form of programmed cell death initiated by caspases, participates in the occurrence and development of IS. Because it can increase cell membrane permeability, mediate the release of inflammatory factors, and aggravate inflammation, inhibiting this process can significantly reduce the pathological injury of IS. The nucleotide binding oligomerization domain-like receptor family pyrin domain protein 3 (NLRP3) is a multiprotein complex whose activation is the core link of pyroptosis. In recent years, studies have reported that traditional Chinese medicine (TCM) could regulate pyroptosis mediated by NLRP3 inflammasome through multi-channel and multi-target networks and thus exert the effect against IS. This article reviews 107 papers published in recent years in PubMed, Chinese National Knowledge Infrastructure (CNKI), and WanFang Data in recent years. It has found that the activation factors of NLRP3 inflammasome include ROS, mitochondrial dysfunction, K+, Ca2+, lysosome rupture, and trans-Golgi breakdown. TLR4/NF-κB/NLRP3, ROS/TXNIP/NLRP3, AMPK/Nrf2/NLRP3, DRP1/NLRP3, TAK1/JNK/NLRP3 signaling pathways regulate the initiation and assembly of the NLRP3 inflammasome, subsequently induce pyroptosis, affecting the occurrence and development of IS. TCM can affect the above signaling pathways and regulate the pyroptosis mediated by NLRP3 inflammasome, so as to play a protective role against IS, which provides a new entry point for discussing the pathological mechanism of IS and a theoretical basis for developing TCM treasure house.